Microstudies on Thermal and UV Treated Silicone-acrylic Paints with different Pigment Volume Concentrations - K.W, Chew; A.K, Arof; A.H, Yahaya; R, Puteh; R, Yahya (Malaysian Journal of Science, 2002)
The effect of pigment volume concentration (PVC) on morphology of pigments particles employed in the siliconeÃ¢â‚¬â€acrylic compositions suitable for high temperature corrosion protection application, has been investigated using SEM. Silicone-acrylic based paints with 50% silicone resin have been selected to prepare paints with PVC values from 10% to 60%. The paints were applied on mild steel panels of size of 5cm x 7.5cm. After curing for one week, the panels were subjected to 24 hours of heating at temperature ranging from room temperature up to 300Ã‚Â°C and 400 hours of UV weathering. After the corrosion test, SEM micrographs were taken to investigate the gloss, rusting and adhesion properties of the coating films.